Comparative Analysis of the Influence of Empagliflozin and Dapagliflozin on the Course of Heart Failure with Associated Pathology - Kulaiets, Nadiia M. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To compare the effectiveness of empagliflozin and dapagliflozin on the course of heart failure (HF) in patients with concomitant pathology. Materials and methods. We examined 398 Caucasian patients with HF on the background of post-infarction cardiosclerosis, aged 58 (54.00-67.00) years (198 women and 200 men). Of these, 226 (56.8%) had persistent atrial fibrillation (AF), 102 (25.6%) had type 2 diabetes mellitus (DM), and 52 (13.1%) had a combination of DM and AF. Reduced left ventricular ejection fraction (LVEF) of ≤40% was observed in 167 patients (42.0%); in 133 (33.4%) patients, LVEF was from 41% to 49%; 98 (24.6%) patients had preserved LVEF (≥50%). The levels of thyroid-stimulating hormone, free T3, free T4, blood glucose, glycated hemoglobin, galectin-3, ST-2, B-type natriuretic peptide, N-terminal pro B-type natriuretic peptide were determined. Registration of electrocardiogram, daily electrocardiography monitoring, and standardized echocardiographic examination were performed during hospitalization and after 1 year. From the first days of inclusion in the study, a sodium-glucose cotransporter 2 inhibitor was prescribed to all the patients, regardless of the presence of DM. The study participants were divided into two groups: the I group included 187 (47%) patients who took dapagliflozin 10 mg daily for a year, the II group included 211 (53%) patients who took empagliflozin at a daily dose of 10 mg. The groups did not differ in terms of the use of β-blocker with different pharmacological properties (bisoprolol or carvedilol) (p = 0.977). Over the course of the year, the patients were observed, taking into account the presence of rehospitalization due to HF decompensation. Statistical analysis was performed using the programs Statistica for Windows Release 10.0 and MedCalc® (Statistical Software version 22.020). Results. In HF patients with moderately reduced LVEF with sinus rhythm without DM, who took empagliflozin, the risk of re-hospitalization was lower compared to those who took dapagliflozin (odds ratio [OR] = 0.136 [0.030-0.623]; χ2 = 5.608, p = 0.018). In the group of HF patients with preserved LVEF with sinus rhythm without DM, who took empagliflozin, compared to the group of patients on dapagliflozin, there was a trend towards lower one-year mortality (χ2 = 3.600, p = 0.058). The frequency of re-hospitalization in HF patients with AF and concomitant DM was lower (by 18.5%; χ2 = 5.122; p = 0.024) when using empagliflozin. Analysis of Kaplan-Meier curves showed that HF patients with a concomitant combination of AF with DM who took empagliflozin, compared to those on dapagliflozin, had a lower probability of re-hospitalization during 12 months (by 18.5%; χ2 = 6.938; p = 0.008). The mean time to the occurrence of the event in the group of HF patients who took empagliflozin was 5.3 ± 0.7 months against 3.1 ± 0.3 months in dapagliflozin patients (OR = 0.389 [0.193-0.786]; p = 0.008). Conclusions. Empagliflozin compared to dapagliflozin is more effective in reducing the risk of re-hospitalization in HF patients with sinus rhythm with a moderately reduced LVEF without type 2 DM (OR = 0.136, p = 0.018) and in the concomitant combination of AF and type 2 DM (without taking into account the HF phenotype) (by 18.5%; p = 0.024). The mean time to re-hospitalization in patients with HF with a combination of AF and DM was 2.2 months longer in patients receiving empagliflozin compared to those receiving dapagliflozin (OR = 0.389; p = 0.008). In other groups of patients with heart failure, dapagliflozin and empagliflozin showed the same effectiveness.